Warthy-Basaloid Squamous Cell Carcinoma of Penile – Case Report - Domian, Natalia; Młynarczyk, Grzegorz; Kasacka, Irena (Frontiers in Oncology, 2021)
Objective The aim of the study was to present a case of penile squamous cell carcinoma and immunohistochemical identification and evaluation of E-cadherin and β-catenin expression. Methods We are presenting a 70-year old man with a variant of penile squamous cell carcinoma with mixed warty and basaloid features. After diagnosis, the patient underwent partial penectomy. Samples taken from the material after surgery were subjected to basic histological staining and immunohistochemical identification of E-cadherin and β-catenin. A Real-time PCR study was conducted to investigate the expression of E-cadherin and β-catenin. Results Routine histopathological examinations revealed the characteristic features of warty-basaloid squamous cell carcinoma. In the case studied, a positive immunohistochemical reaction was observed for E-cadherin and β-catenin. QRT-PCR analysis showed a statistically significant decrease in E-cadherin expression in tumor samples compared to healthy tissue. In contrast, expression of the gene encoding β-catenin was slightly higher in tumor samples compared to normal tissue. Conclusions The reduced level of the complex of adhesive elements, E-cadherin-β-catenin, disturbs cell differentiation, promotes a more invasive phenotype-stromal infiltration and the formation of distant metastases. In the described case of the penile tumor, a decrease in E-cadherin expression was noted, which could be related to the occurrence of neoplastic infiltration of the spongy body space. In summary, E-cadherin and β-catenin expression and the immunoreactivity of these proteins are expressed at different levels in tumor cells and in penile interstitial cells. Regulation of expression during various physiological and pathophysiological processes indicates a potentially important role of E-cadherin and β-catenin in cell proliferation and adhesion.